(untitled) (Experimental biology, 2016)
New methods and results of study of precursors of the earthquakes registered by bioindicators are shown in the article. The obtained data on the testimonies of device of indicator of seismic danger of ИСО- 5 are preceded to the taking place earthquakes. Bioindicators are sensitive systems that respond to changes in gravitational, electromagnetic fields, as evidenced by changes in the amplitude of voltage and micro under the full moon (maximum gravitational effect on the Earth’s crust) and to change the solstice in different seasons. In addition, it was possible to show that in the region of seismic tension (foothills Dzhungar), where the city of Taldykorgan observed abnormal bursts of power miktorotok amplitude and voltage, particularly clearly visible in a few tens of hours before the start of a seismic event in Taldykorgan and neighboring regions.